2019
DOI: 10.1007/s00394-019-02065-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary markers of hydration during 3-day water restriction and graded rehydration

Abstract: Purpose This investigation had three purposes: (a) to evaluate changes in hydration biomarkers in response to a graded rehydration intervention (GRHI) following 3 days of water restriction (WR), (b) assess within-day variation in urine concentrations, and (c) quantify the volume of fluid needed to return to euhydration as demonstrated by change in U col . Methods 115 adult males and females were observed during 1 week of habitual fluid intake, 3 days of fluid restriction (1000 mL day −1 ), and a fourth day in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This type of testing has been evaluated for exercise-induced dehydration in sports medicine [1][2][3][4][5], and they also seem to be relevant to hospital care [6][7][8][9][10][11][12][13]. The validity and importance of urine analysis as a surrogate measure of the fluid balance in the general population is still unclear, but the issue has recently caught interest [14,[24][25][26][27][28]. The present results confirm that concentrated urine is due to low consumption of water, but the answer to the second part of the primary hypothesis is mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of testing has been evaluated for exercise-induced dehydration in sports medicine [1][2][3][4][5], and they also seem to be relevant to hospital care [6][7][8][9][10][11][12][13]. The validity and importance of urine analysis as a surrogate measure of the fluid balance in the general population is still unclear, but the issue has recently caught interest [14,[24][25][26][27][28]. The present results confirm that concentrated urine is due to low consumption of water, but the answer to the second part of the primary hypothesis is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Stookey et al reported an increase in body weight of 0.5 kg, but only after 4 weeks of increased water intake amounting to 1 L/ day [27]. Following a 3-day fluid restriction to 1 L/day in volunteers with normal fluid intake, an additional 1.5 L/day was needed to regain normal urine colour, which is another index of concentrated urine, within 24 h [28]. Thus, a quite large change in water intake is needed to make the kidneys change from conserving to excreting water.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted using baseline data collected on 123 male and female volunteers that were part of a study evaluating urine color as a marker of change in daily water intake [31]. Participants aged 18–45 years were recruited through ListServ e-mail announcements, and flyer placement around Laramie, Wyoming.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, our study also demonstrated a weak correlation between the clinical dehydration status assessed by clinician and RGB urine colourimetry. A study of a 3-day voluntary water restriction resulted in increases in urine osmolality, urine colour, and urine SG [27], a finding similar to that of 24-hour controlled dehydration [14]. Hydration category based on the blue component of RGB urine colourimetry as proposed by Jeanette et al PLOS NEGLECTED TROPICAL DISEASES (18) showed that subjects with poor oral intake were the ones with serious dehydration, while the patient with dengue shock had serious dehydration and those with warning signs had significant or serious dehydration.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%